The Utilisation of Human Embryonic Stem Cells: An Islamic Law Perspective - Mardhiyyah Munir Ja’afar (International Journal of Advanced Science and Technology, 2020)
Human embryonic stem cells are used for the treatment of conditions such as infertility, spinal cord injuries, genetic disorders, neurological and haematological diseases and are suggested as means of curbing graft rejection. Although new findings indicate that the body may reject transplanted human embryonic cells. The significance of human embryonic stem cells lies in their ability to proliferate and differentiate into different cells. Despite their prospective benefits, their utilisation raises issues from the perspectives of medicine, ethics, law and Islam. From the perspective of Islam, the two central issues that must be addressed in the context of using human embryonic stem cells are consent and abortion. This paper adopts a doctrinal research and discusses the Islamic law perspective on the utilisation of human embryonic stem cells. It is found out that willful termination of embryos for the sole purpose of obtaining cells is an act of aggression in Islam.